Sustainable Infrastructure Development Strategy in Tamansari Village to Improve Community Quality of Life - Wahyu Ferliansyah; Aula Izatul Aini (Electronic Journal of Education, Social Economics and Technology, 2025)
Sustainable infrastructure development in rural areas is crucial for enhancing the quality of life within communities. Tamansari Village, with its unique potential and challenges, requires a comprehensive approach that takes social factors into account. Effective infrastructure not only improves accessibility but also fosters inclusive social development, strengthens community solidarity, and empowers local populations. This study employs a descriptive qualitative approach, focusing on infrastructure development strategies. Primary data is gathered through direct interviews with community leaders and the village head, while secondary data is sourced from previous research findings. Tamansari Village, located in Tegalsari District, Banyuwangi Regency, East Java, has made significant progress in its development. The concept of sustainable development emerged from the consensus among commission members that many infrastructure projects carry risks in managing village finances. Mr. Khoirul Anam, the Village Secretary, highlights the importance of careful planning and execution to ensure that development is not just temporary but yields long-term benefits. The four key elements—planning, implementation